(untitled) (Czech Journal of International Relations, 2014)
Jan Hodač, Lubor Lacina, Petr Strejček: Evropské křižovatky. 2. vydání. Brno: Barrister & Principal, 2014, 184 stran, ISBN 978-80-7485-018-9.